PENINGKATAN MOTIVASI BELAJAR SISWA PADA MATA UJIAN NASIONAL DENGAN MENGGUNAKAN MODEL BELAJAR INQUIRY DI SEKOLAH DASAR SE-KECAMATAN INDRALAYA SELATAN KABUPATEN OGAN ILIR - Lusiana Ekawati; Lince Sri Purwani; Muhammad Adi Putra; Mustar Mustar; Muqorrobin Muqorrobin (MAP Program Pascasarjana Universitas Sjakhyakirti, 2021)
The Minister of Education and Culture hopes that the regional and central governments can move together in equalizing access and quality of education in Indonesia. Equitable access and quality of education need to be accompanied by other initiatives by local governments, such as redistribution of teachers to schools that lack teachers. The UN was abolished because of COVID-19, it needed a passing standard, the Minister of Education and Culture Nadiem Makarim overhauled the textbooks in schools and released a Learning Program broadcast by TVRI. The implementation of the 2020 UN starting from schools and madrasas at the elementary (SD/MI), junior high (SMP/MTS) and upper secondary (MA/SMA) levels has been officially canceled due to the COVID-19 coronavirus pandemic. tirto.id. The government has officially determined that all 2020 National Examinations (UN 2020) will be abolished. The policy for eliminating the 2020 UN is starting from schools and madrasas at the elementary (SD/MI), junior high (SMP/MTS) and upper secondary (MA/SMA) levels. The spread of the COVID-19 outbreak is predicted to continue until April, so it is impossible for us to force students to gather to carry out the National Examination in the midst of the COVID-19 outbreak in Indonesia. as a form of accountability of education providers to interested parties. It is further stated that the evaluation is carried out by an independent institution on a regular, comprehensive, transparent, and systematic basis to assess the achievement of national education standards and the process of monitoring the evaluation must be carried out on an ongoing basis. The monitoring and evaluation process is carried out continuously and continuously, in the end, it can improve the quality of education. In research in South Indralaya District, Ogan Ilir Regency, it has been trying to improve student learning motivation well. This can be seen from how teachers in teaching who always try to increase the enthusiasm of their students to learn both at school and outside school, apply student learning motivation with existing theories, although formally it can be seen from how the efforts that have been made This is done by teachers in providing motivation to their students, including giving gifts or rewards in the form of goods, values ​​or words of praise. By growing interest by changing the forms of teaching such as changing seats, learning outside the classroom and so on. Explaining the learning objectives by explaining the learning objectives before entering the material to be discussed. Giving tests and assignments by giving homework, tests, and other tasks. And Give a value or number by giving a value to the results of student work, both school assignments and homework (PR) by doing group assignments.